Penerapan Metode Pembelajaran SQ4R untuk Meningkatkan Keterampilan Membaca Narrative Text - Karmila, Karmila (Paedagogie, 2019)
This study aims to find out how SQ4R strategy improves students’ reading skills of Narrative Text. The subjects are 36 students of X IPS 3. It uses CAR design which is carried out in 2 cycles. The data collection is conducted through classroom observation and test. The results showed that there is a match between the learning of Narrative Text Reading and the application of the SQ4R strategy. Students look enthusiastic about learning activities. Overall, the use of the "SQ4R" method can improve narrative text reading skills. This method is in accordance with the character of reading activities of narrative text and can be applied to other reading classes.